(untitled) (Research, Society and Development, 2020)
Wheat is a crop rich in nutrients. In Brazil, about 130,000 properties produce the cereal, involving 800,000 people. Due to its rheological properties, that is, the extensibility capacity of this cereal stands out in the manufacture of breads, in addition to the increasing use of flour in the food industry. Thus, the use of some physical-chemical analysis to determine the quality of wheat flour according to the normative instruction from Agriculture, Livestock and Storage Ministry (MAPA) document nº 8/2005. Wheat flour samples of type 1 (A, B and C) were acquired in a supermarket located in the city of Belém / PA, posteriorly sent to the Centro de Tecnologia Agropecuária - CTA at the Universidade Federal Rural da Amazônia (UFRA), to determine granulometry, grease acid, protein, humidity and ashes. Regarding to granulometry analysis, samples A and C were above the tolerance values proposed by the Ministry of Agriculture and Livestock - MAPA. Grease acid and humidity were inside to MAPA tolerance standards for all samples. In ashes determining, the values showed that all three samples were out of the quality standard, in addition, about protein content, the samples were also characterized as out of type. Therefore, there is a need for better inspection by the responsible authorities, since cultivation conditions until the final quality control of the product.